SCIENTIFIC AND ORGANIZATIONAL FUNDAMENTALS OF THE TRANSFER OF TECHNOLOGIES OF SCIENTIFIC DEVELOPMENTS - Rasevych, Volodymir; Rasevych, Iryna (Social Economics, 2024)
The article was investigated the ways of activating the innovative development of agricultural enterprises. It was confirmed the importance of strengthening the innovative development of the agricultural industry, it was assessed its main trends were determined, and the level of efficiency of innovative activity. It was determined methods and tools for stimulating the innovative activity of agricultural enterprises. It was defined an evaluation of the constituent elements of the organizational and economic mechanism of the innovative development of the agro-industrial complex. It was developed scientific and organizational approaches to the transfer of knowledge-intensive products in agro-industrial complexes. It was determined the current state and prospects of innovative development of agro-enterprises. It was provided proposals for filling the agro-food market with innovative products. It was shown that increasing the activity of innovative activities of agricultural enterprises will ensure increased competitiveness and economic efficiency of production. It was noted that in order to intensify innovation processes in agro-industrial production, an important condition is to overcome obstacles, namely, limited financial capabilities, weak support from the state and low demand for innovative developments by consumers. It was emphasized the necessity to solve the problem of practical application of the results of scientific research and development. It was identified ways of their effective commercialization that will facilitate the dissemination of developments and increase the competitiveness of national agricultural products in the domestic and global markets and will assist to bridge the gap between science and industry by strengthening cooperation and ensuring that innovations reach their potential market application. The obtained results are the basis for further innovations and investments in the development of the agricultural production system of research institutions and their research and experimental bases.